IDEOLOGICAL AND ARTISTIC CONCEPTS IN THE CREATIVE WORKS OF ULIANA HLYNCHAK WITHIN THE UKRAINIAN-CANADIAN CULTURAL SPACE - Vivcharyk, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article analyzes the work of Uliana Hlynchak in the context of modern Ukrainian diaspora literature. The main attention is focused on the features of the writer’s artistic discourse, in particular, on the representation of cultural memory, national identity in a multicultural environment. The genre and poetic characteristics of the poetic and prose works are studied, the role and place of symbolic details as cultural markers of the writer’s artistic world are clarified. The article emphasizes that the author’s work performs an important representative function, since through the artistic word she conveys information about modern military events in Ukraine to an international audience. Special attention is paid to the analysis of the poem about the war “Ukrainian Lullaby”, which became a song and was performed at the Ukrai-nian Festival in Toronto in 2025. It is found that poetic images of women who experience losses but do not break acquire symbolic meaning and represent the idea of spiritual endurance and national dignity. It is illustrated that the work of Uliana Hlynchak is an important component of the modern Ukrainian diaspora literary process, as it introduces Canadian readers to Ukrainian culture and history, and also artistically reveals modern military events.